Global solution of the initial value problem for the focusing Davey-Stewartson II system - Lakshtanov, Evgeny (2020)
We consider the two dimensional focusing Davey-Stewartson II system and construct the global solution of the Cauchy problem for a dense in L 2 (C) set of initial data. We do not assume that the initial data is small. So, the solutions may have singularities. We show that the blow-up may occur only on a real analytic variety and the variety is bounded in each strip t ≤ T.